2015
DOI: 10.1080/2162402x.2015.1022301
|View full text |Cite
|
Sign up to set email alerts
|

Progressive loss of anti-HER2 CD4+ T-helper type 1 response in breast tumorigenesis and the potential for immune restoration

Abstract: Genomic profiling has identified several molecular oncodrivers in breast tumorigenesis. A thorough understanding of endogenous immune responses to these oncodrivers may provide insights into immune interventions for breast cancer (BC). We investigated systemic anti-HER2/neu CD4 C T-helper type-1 (Th1) responses in HER2-driven breast tumorigenesis. A highly significant stepwise Th1 response loss extending from healthy donors (HD), through HER2 pos -DCIS, and ultimately to early stage HER2 pos -invasive BC patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 37 publications
7
58
0
Order By: Relevance
“…In our ongoing experiments, we revealed an enhanced IFN‐γ production after stimulation of TIL with bsscFv [HER2xCD3] or tribody [(HER2) 2 xVγ9]. This is in line with the data reported by Datta et al., which demonstrated that the treatment of breast cancer patients with HER‐2‐pulsed dendritic cells restore a depressed Th1 response mediated, for example, by IFN‐γ release …”
Section: Discussionsupporting
confidence: 90%
“…In our ongoing experiments, we revealed an enhanced IFN‐γ production after stimulation of TIL with bsscFv [HER2xCD3] or tribody [(HER2) 2 xVγ9]. This is in line with the data reported by Datta et al., which demonstrated that the treatment of breast cancer patients with HER‐2‐pulsed dendritic cells restore a depressed Th1 response mediated, for example, by IFN‐γ release …”
Section: Discussionsupporting
confidence: 90%
“…Although this deficit does not appear to be corrected by surgery, radiation, chemotherapy, or HER2 targeted monoclonal antibodies, we showed that it can be corrected by HER2 peptide pulsed DC1 vaccination resulting in long term maintenance of anti-HER2 immune response. 9,10 These results support the multivalent targeting of HER2. Anti-HER2 Th1 cells together with HER2 directed antibodies may enhance the tumoricidal effects of anti-HER2 CD8 C Tcells and facilitate the potential use of checkpoint inhibitors in the treatment of HER2 pos breast cancer.…”
supporting
confidence: 64%
“…Unfortunately, we have previously shown that there is an early and progressive loss of anti-HER2 CD4 C Th1 response in breast tumorigenesis-healthy patients have a strong anti-HER2 CD4 C Th1 immune response that is decreased in patients with ductal carcinoma in situ and nearly absent in patients with invasive breast cancer. 9 We also showed that the magnitude of the immune response correlates with clinical outcomes-a depressed anti-HER2 CD4 C Th1 immune response correlates with an increased risk of recurrence, and a robust response correlates with an increased rate of pathologic complete response following neoadjuvant chemotherapy. Although this deficit does not appear to be corrected by surgery, radiation, chemotherapy, or HER2 targeted monoclonal antibodies, we showed that it can be corrected by HER2 peptide pulsed DC1 vaccination resulting in long term maintenance of anti-HER2 immune response.…”
mentioning
confidence: 58%
“…Patients with metastatic HER2 þ breast cancer have multiple FDA approved anti-HER2 therapies available, yet no curative options have been developed and the majority of patients will eventually die of progressive disease. Although ICB has shown clinical activity in many tumor types, including a few long-term survivors, responses in HER2 þ breast cancer are modest, perhaps reflecting a less robust adaptive immune response in HER2-driven breast cancer (9). Rather than relying on enhancing the naturally occurring adaptive immune response to tumor neoepitopes, we developed an immunization strategy that would expand HER2specific T cells and antibodies to provide effective antitumor responses that complement current HER2 targeting SOC regimens.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to fewer somatic mutations and therefore fewer tumor neoepitopes, but even treatment-refractory tumors generally continue to overexpress HER2 (8). It is also recognized that HER2-specific immunity is lost throughout the progression of HER2 þ disease (9). Accordingly, there is great interest in enhancing adaptive immune responses to HER2, including cancer vaccines that activate broad, HER2-specific T-cell and antibody responses, and how such therapeutics can be integrated into the current management of metastatic HER2 þ breast cancer.…”
Section: Introductionmentioning
confidence: 99%